Insulators for 2D nanoelectronics: the gap to bridge - Yury Yu. Illarionov; Theresia Knobloch; Markus Jech; Mario Lanza; Deji Akinwande; Mikhail I. Vexler; Thomas Mueller; Max C. Lemme; Gianluca Fiori; Frank Schwierz; Tibor Grasser (Nature Communications, 2020)
The lack of scalable, high-quality insulators is a major problem hindering the progress on electronic devices built from 2D materials. Here, the authors review the current state-of-the-art and the future prospects of suitable insulators for 2D technologies.